Airplane pilot coupling: a review of the state-of-the-art knowledge with focus in flight test. - Maurício Faustino Oliveira (2004)
Airplane-Pilot Coupling (APC) is the current denomination of unwanted dynamic couplings between the airplane an pilot that can occur in specific circunstance, leading to instability an otherwise stable system. APC events can be non-oscillatory but the most common are oscillatory, commonly called Pilot-Involved Oscillations (PIO). Most of the previous and on going researches have tried to understand, predict and avoid APC events. Understanding is based in many studies that include analyses of real cases of APC, interpretation of pilot plus airplane as a closed-loop system and classification of APC events according to characteristics like degree of nonlinearity or frequency and amplitude of the oscillations. Prediction is based in analytical criteria; many of them are currently under development. Such criteria are intended to be applied during airplane design in order to decide whether determined configuration is (or is not) susceptible to APC events. Avoidance is based in the combination of concepts resulting from correct understanding of the APC phenomenon with application of appropriated prediction criteria. This combination should make it possible to develop a good design. But this is not sufficient to guarantee a very low possibility of an APC event occur during the airplane operacional life. Therefore, to complement the avoidance process it is necessary to plan and to perform a specific flight test program. This text is an effort that attempts to cover the most import APC related points, named undestanding, prediction and avoidance. However, the focus of the present text is in the third point. More specifically, the main goal of text is to propose a methodology - including specialized maneuvers - to conduct a flight test program dedicated to APC. This is done in a way that a methodology constituted by three phases is proposed. In the first phase only low bandwidth handling qualities* at safe concitions, are tested. This phase can be understood as a "familiarization" testing. In the second phase the high bandwidth handling qualities* are tested, always using tracking manueuvers, that require the evaluation pilot to drive the airplane to track an specific signal as aggressively and assiduously as possible. In the third phase pilots must conduct evaluation of the airplane handling qualities during situations. Complementing the maneuvers performed during the flight test program above mentioned, it is necessary to apply suitable tools in order to "measure" the APC susceptibility of the tested airplane. In this text the current main tools are described. They are basically pilot comments, rating scales (that are based pilot opinion) and frequency domain data analyses (that are based in the obtainment of the frequency response from test data).